Disclosure of Sibling Sexual Abuse by Hospitalized Adolescent Girls: Three Case Reports - Carretier, Emilie; Lachal, Jonathan; Franzoni, Nina; Guessoum, Selim Benjamin; Moro, Marie Rose (Frontiers in Psychiatry, 2022)
Although sibling sexual abuse (SSA) may be the most common type of intrafamilial sexual abuse, it has not been widely studied. The lack of studies makes it very difficult for clinicians to create a comprehensive framework about this complex phenomenon, particularly in comparison with other forms of intrafamilial sexual abuse, such as father-daughter incest. SSA is still underrecognized and underdisclosed but it has the potential to be every bit as harmful as sexual abuse by a parent. The topic rarely finds its way into the more general psychiatry or social work literature. It is imperative to increase healthcare practitioners' awareness of this complex subject to improve their ability to listen to, detect, and manage the disclosures of SSA in adolescent populations. This paper presents vignettes of three 13-to-15-year-old adolescent girls who disclosed SSA during inpatient hospitalization in an adolescent psychiatric and medicine department. These cases illustrate the complexity of SSA, which has been associated with a wide spectrum of both mental and physical symptoms. Adolescent victims of SSA experience serious distress, with various and numerous psychiatric manifestations, including but not limited to depression and suicide attempts, addictive behaviors, post-traumatic stress symptoms, and eating disorders. Physical symptoms should also alert practitioners: adolescent survivors are more likely to be affected by somatic complications such as sexually transmitted diseases, chronic pain, urogenital symptoms, and nutritional disorders. We offer some recommendations to improve the detection and support of distressed adolescents disclosing SSA. Listening to them and offering a protective multidisciplinary response can limit the lasting damage and contribute to the repair process.